Frances Baumgarten’s empirical research of lie (falsehood) in children and teenagers - ZEIDLER, WŁODZISŁAW (Studia Psychologica: Theoria et praxis, 2016)
At the turn of 19th and 20th century Frances Baumgarten’s empirical research was one of the positive influences in the development of psychology, otherwise clearly hampered by political barriers and ideological influences. It was particularly important for the development of psychological terminology in each of the emerging new countries. Frances Baumgarten’s research, which was done in 1914 and published in several publications in Polish 13 years later, shows one of the more interesting and particularly valuable examples of the development of empirical research methodology and is the evidence of high development and specialization of Polish psychological language.